Adaptive Super-Twisting Sliding Mode Control of Permanent Magnet Synchronous Motor. (31st August 2021) - Lu, Chao; Yuan, Jing
Abstract : The work has developed an innovative speed loop controller for the permanent magnet synchronous motor (PMSM) system. The main advantage of the presented method lies in the fact that the boundary of the lumped disturbance is not required. Under this case, the severe chattering caused by the inappropriate choice of parameters can be avoided. Finally, the simulation and experimental consequences are given to demonstrate the efficiency of the proposed algorithm used to control a PMSM system subject to the lumped disturbance.